DEVELOPMENT OF MULTIMEDIA LEARNING BASED ON MACROMEDIA FLASH 8 AS A SOURCE OF SELF-LEARNING ON THE DIGESTIVE SYSTEM MATERIALS - Mangombar M.T. Pakpahan; Mariaty Sipayung (Universitas Negeri Medan, 2021)
This study aims to determine the feasibility level of learning multimedia developed using Macromedia Flash 8 software on the food digestive system material as a source of student self-study based on the responses of material experts, media experts, field teachers, and students. This study uses a 4-D model of instructional development design, including the stages of definition, design, development, and dissemination, limited to the limited deployment stage to see students' classical learning completeness. This research was started in September 2020 – February 2021. The product trial was conducted at the GKPI Padang Bulan Private High School, Medan. The results showed that (1) learning multimedia developed using Macromedia Flash 8 software on the food digestive system material in humans had been compiled with input from validators, biology educators, and students; (2) the learning multimedia developed is considered suitable for use in biology learning in terms of the assessment of material experts with an average score of 4.5, media experts with an average score of 4.4, field of study teachers with an average score of 4.9, and students with an average score of 4.7; and (3) 97% of students completed learning the material on the human digestive system after using learning multimedia based on Macromedia Flash 8. As an implication, the developed learning multimedia is expected to help the biology learning process, whether online or face-to-face.